Are There Gender Differences in How Students Write Their Essays? An Analysis of Writing Processes. Issue 2 (25th March 2019) - Zhang, Mo; Bennett, Randy E.; Deane, Paul; van Rijn, Peter W.
Abstract: This study compared gender groups on the processes used in writing essays in an online assessment. Middle‐school students from four grades responded to essays in two persuasive subgenres, argumentation and policy recommendation. Writing processes were inferred from four indicators extracted from students' keystroke logs. In comparison to males, on average females not only obtained higher essay scores but differed from males in their writing processes. Females entered text more fluently, engaged in more macro and local editing, and showed less need to pause at locations associated with planning (e.g., between bursts of text, at sentence boundaries). That these differences were detected after controlling for essay scores suggests that they cannot be attributed solely to disparities in group writing skill.